Análise e utilização do indicador antropométrico razão cintura-estatura na avaliação do risco metabólico em adolescentes brasileiros - Lins, Pamela Rodrigues Martins (2019)
Adolescence is a peculiar phase of human development, marked by intense physical, sexual, and behavioral transformations. Changes in the distribution of body fat during adolescence are strongly influenced by sexual maturation, and this phase is considered one of the critical periods for the onset of obesity, which in turn may be associated with a set of metabolic alterations such as dyslipidemias and insulin resistance. In this point of view, the objective of this study was to evaluate the relation of the Waist-to-height ratio (WHtR) with metabolic alterations in adolescents, according to the stage of sexual maturation. Variables of sexual maturation (Tanner planks), anthropometric variables (weight, height, waist circumference (CC), and biochemical variables (fasting glucose, fasting insulin, HOMA-IR, total cholesterol and fractions c and HDLc) and triglycerides), as well as demographic (sex and age). Data from 37,759 Brazilian adolescents aged 12-17 years, of both sexes, who participated in the national population-based study "Study of Cardiovascular Risks in Adolescents - ERICA" were analyzed. All analyzes were done in the program Stata 14.0 SE. The adolescents were described according to sex and stage of sexual maturation and were classified according to excess abdominal adiposity, according to the WHtR score. Linear regression models were constructed to observe the relationship between each of the metabolic variables, HOMA-IR, triglycerides, HDL-c, LDL-c, total cholesterol and fasting insulin, and the WHtR. The coefficients of determination of each equation (r2) and the values of the regression coefficients obtained were calculated. The determination of the best cutoff points for predicting insulin resistance, stratified by sex and stratified by sex and stage of sexual maturation, constructed an ROC curve for each group. The areas under the ROC curve and the confidence intervals (95% CI) were used to assess the diagnostic value of the WHtR. The mean age of the adolescents was 14.7 (± 0.008), the majority of the boys were in the final stages of maturation and the girls had a distribution around 30% in stages II, IV and V. Abdominal obesity evaluated by WHtR was more prevalent at the end of sexual maturation in girls and at maturation in boys. The relation of the WHtR varied according to the parameter evaluated. Insulin and HOMA-IR metabolic indicators presented the highest coefficients of determination in the regression equations obtained in the study, especially among boys (r ² 0.43 and r ¼ 0.40, respectively). After analyzing ROC, we observed that. The best cutoff points of rCERs stratifying only by sex were 0.45 for females and 0.44 for males. When Tanner stratification was included, cut-off points were reduced along maturation stages in boys and female adolescents showed an inverse behavior. Because it is easy to measure and interpret, it can be used in risk screening for metabolic changes, especially insulin resistance, especially in boys who initiate sexual maturation.